A model of tournament incentives with corruption - Bin Wang; Yu Zheng (Queen Mary University of London, School of Economics and Finance, 2018)
We provide a theory of how growth, corruption, and a low-powered public-sector pay scale coexist in a stable equilibrium in the early stage of China's development. The regionally decentralized authoritarian regime of China features lower-level government officials competing for promotion to a higher level in the government by generating local economic growth, and calls for high-powered incentives to elicit effort from the the officials. However, this is at odds with the generally low-powered public-sector pay scale in China. We propose a principal-agent model, where the principal represents the Chinese people's desire to pursue economic growth and the agents are the government officials delegated with production tasks and organized in a tournament, to address how a low-powered pay scale can effectively elicit effort in a tournament infested with widespread corruption.
Keywords: D73; J45; O43; P26; 330; Institution; Tournament; Corruption; China